The student teaching program of Normal schools in Khuzistan, Iran - Javaherforoush-Zadeh, Abdul-Rahim 1932- (s.n.], 1970)
The study is an assessment and evaluation of the student teaching program of normal schools in Khuzistan, Iran. An analysis of the findings have been secured through checklists and questionnaires. The results of the study which include objectives, scope and nature, preparation, organization, and supervision and evaluation, point out the needs of the present educational system and the tentative ways or solutions of addressing the needs.